Psycho Social Factors in Adolescent Suicides- A Psychological Autopsy based Study - Krishna Kumar Siva Sankara Narayanan1 , MuthukumarDuraiappa2, Prajith Thekke Madathil1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
BACKGROUND: Suicides among adolescents in India have become an alarming problem, especially among students. This study is to find out the recent and remote psychosocial and disease related stress and adverse life events that could have led these young people to commit suicide.MATERIAL AND METHODS: It is a Cross sectional study on adolescent suicides with history and postmortem findings being consistent with suicideconducted at Department of Forensic Medicine, Government Medical College, Kozhikode, Kerala state .FINDINGS: Informants of 55 cases were interviewed with the help of questionnaire.Most of the suicide victims belonged to upper middle class category.Maximum number of suicidal deaths are seen in victims having 1 sibling, living in a nuclear family.History of suicidal deaths among the family members of the suicide victim is seen in 7 out of 55 cases.Mood of maximum number of cases before the suicide attempt in the recent past, say 2 weeks, was depressed. Maximum number of suicide attempts were seen in the evening, mostly after the school and college working hours.Academic performance of 40.0%cases was average.10.9% were socially isolated. 14.5% had a history of previous suicide attempt. 14.5% had shown anger, aggression and impulsivity in the recent past, say 2 weeks. CONCLUSION: The main purpose of this study is to find out the stressors that could have led these adolescents to commit suicide and to suggest a few strategies to prevent the suicides in the future.